Simulation of Direct Normal Irradiation (DNI) in Alentejo with the atmospheric MESO-NH model: several case studies - Salgado, Rui (2018)
The short and medium range forecast of DNI by operational numerical weather prediction models is very recent and its quality should be accessed and improved. The European Centre for Medium-Range Weather Forecasts (ECMWF), for example, only provides DNI forecasts from 2014. Inside the ECMWF model, the solar radiative quantities are computed by the Short Wave (SW) scheme which results from successive developments from the initial Morcrette version [1]. The same radiative code is in use by other NWP models, namely by the French limited area AROME model, which runs operationally at the Portuguese meteorological service (IPMA) for three domains (continental Portugal, Madeira and Açores) and by the non-hydrostatic research Meso-NH model [2]. In order to test and eventually improve the radiative forecasts it is important to compare the model DNI results against observed data. The existence of a network of DNI radiative stations (equipped with SOLYS 2 sun trackers) in Alentejo operated by the University of Évora under the research activity of ST Renewable Energy Chair (ST-REC) and the Institute Earth Sciences (ICT) provides conditions to such kind of validation studies. In this context, it was proposed to the students of the atmospheric modeling course of the doctoral program in Earth and Space Sciences (University of Évora), the carrying out of case-studies simulations with the Meso-NH atmospheric model. Showing the results of these exercises and the comparison against measurements in Évora is the purpose of this works. All the simulations were performed over the same domain, centered in Évora, covering the Alentejo and Algarve regions with an horizontal resolution of 3x3 km2. The initial and coupling conditions were provide by the ECMWF 6-hourly analysis. The selected case-studies coincides to periods in which data of atmospheric field campaigns are available, allowing a better validation of the simulations. The periods considered were: 25-25 July 2014 (ALEX 2014 Intensive Observation Period – www.alex2014.cge.uevora.pt); 4-5 June 2015 (OBELIX I); 4-5 July 2016 (OBELIX II) and 9 and 10 January 2017 (www.alop.ict.uevora.pt).